A inoculação ruminal de Enterococcus faecalis é eficiente no controle da intoxicação por monofluoroacetato de sódio em ovinos? - Dias, Geovanny Bruno Gonçalves (2015)
From the group of plants that cause sudden death in livestock in Brazil, seven of which contains sodium fluoroacetate (MFA) as toxic principle. MFA cause blockage of the Krebs cycle and subsequent accumulation of citrate in the tissues. The movement of animals that are intoxicated triggers the clinical signs and cause the death with acute evolution. One envisaged alternative to preventing poisoning is the ingestion of nontoxic doses of plants containing the MFA. It is suggested that the resistance occurs due to proliferation of microorganisms that express the MFA degrading gene fluoroacetate dehalogenase and that the MFA is degrade in the rumen. This study aimed to determine whether E. faecalis FY09, JQ661270.1 and FY08, JQ661271.1, isolated from bovine rumen, degrade MFA in vivo and can be used for detoxification of plants containing MFA. To carry out this experiment, six sheep with an average age of two years old, female, between 35-40 kg, Santa Ines, were divided into two groups of three animals each. The inoculation Group received for three consecutive days, E. faecalis - 30 ml inoculum divided into three doses of 10 ml. The control group received distilled water for the same period. The animals of both groups were kept at rest for 48 hours and after this period, the MFA is provided in a dose of 1.5 mg / kg / Live Weight orally to all sheep. Clinical signs, heart and respiratory rate were obtained at rest every hour, and after 10 minutes of elapsed drive six hours of poisoning. All animals in both groups died between three and eight hours after delivery of MFA. The results indicate that the animals have not developed resistance to MFA after inoculation with E. faecalis.